Internal Flow Field and Loss Analysis of a Magnetic Drive Pump’s Cooling Circuit - Zhenfa Xu; Fanyu Kong; Kun Zhang; Yinfeng Wang; Jiaqiong Wang; Ning Qiu (Energies, 2023)
The cooling circuit is an important component of the magnetic drive pump because it prevents demagnetization of the permanent magnet and damage to the containment shell owing to a high temperature increase. In this paper, the flow field and losses of the cooling circuit of the magnetic pump are discussed and experimentally verified based on numerical simulation methods. Five different lengths of magnetic couplings were designed, and the flow field distribution, cooling flow rate, and loss variation laws of the cooling circuit were analyzed. The results show that the pump flow rate and magnetic coupling length have a minimal effect on the velocity distribution in the cooling circuit. When the magnet length increases from 30 mm to 55 mm, the temperature rise of the cooling circuit and the pressure drop at the gap increase by 23.1% and 25.3%, respectively. When the length of the magnetic coupling remains constant, the cooling flow rate of the cooling circuit falls with an increasing pump flow rate, and it reduces by 8.4% when the pump flow rate increases from 0.7 Q to 1.3 Q. The water friction loss and eddy current loss of the cooling circuit increase with an increase in the magnetic coupling length, while the cooling flow rate decreases. When the magnet length increases from 30 mm to 55 mm, the eddy current losses in the coupling circuit and the water friction losses in the cooling circuit increase by 45% and 35%, respectively, while the cooling flow rate decreases by 13%.